The effects of happiness and hope on executive functions - Lautenbach, Franziska (Frontiers in Psychology, 2025)
The notion that positive emotions always yield positive outcomes is compelling, yet prior meta-analytic findings (19 effect sizes) suggest no impact on executive functions. Limitations have been noted regarding the induction of specific positive emotions and assessment quality, especially for cognitive flexibility and working memory. To expand on this, the current studies induced happiness and hope in college students to examine effects on inhibition, cognitive flexibility (study 1, N = 27), and working memory (study 2, N = 30). Results confirmed successful emotion induction and revealed that cognitive flexibility was significantly higher in the happiness condition than in a neutral condition (p = 0.014, d = 0.427). Findings suggest challenges in experimentally differentiating discrete positive emotions and indicate that not all executive functions are equally affected. Overall, these results lend support to Isen’s facilitator theory but should be interpreted with caution.